Terapi Audio dengan Murottal Alquran Terhadap Perilaku Anak Autis: Literature Review - Anam, Akhyarul; Khasanah, Uswatun; Isworo, Atyanti (Journal of Bionursing, 2019)
Introduction. Child auitism has a disorder in behavior, communication, social interaction and unstable emotions. Austism is a syndrome that results from complex muscle damage and neurodevelopmental disorders. Intervention to the behavior of children with autism can be done by providing murottal audio therapy Alquran.Objective. this study aimed to examine the effect of audio therapy with murottal Alquran on the behavior of austistic children.Methods. Article searches conducted electronically using several databases: Proquest, PubMed, Mendeley, and Google Scholar since 2013-2017. Keywords used are "audio therapy / audio therapy", "Alquran", behavioral disorders?, " autism / autism "; so get 3 articles to be reviewed.Results. Audio therapy with murottal Alquran can decrease autistic child's behavior disorder both in emotion, communication and social interaction compared with music therapy.Discussion. Provision of murottal Alquran therapy provides a positive effect for autistic children to reduce behavioral disorders, murottal therapy Alquran can be done for other disease interventions because this therapy does not cause side effects and safe.Conclusion. Audio therapy with murottal Alquran can decrease autistic child behavior.